2013
DOI: 10.4067/s0718-19572013000300024
|View full text |Cite
|
Sign up to set email alerts
|

Range extension of the non-indigenous alga Mastocarpus sp. along the Southeastern Pacific coast

Abstract: Abstract.-The red macroalga Mastocarpus sp. (Rhodophyta, Gigartinales) has been reported as a non-indigenous species in central Chile. In this area the geographic range described for the species encompasses approximately 200 km, from Cobquecura (36°08'S, 72°48'W) up to Punta Lavapié (37°08'S, 73°35'W). Observations carried out at 22 localities along the central-southern Chilean coast allow us to extend the known range of this species approximately 300 km to the north and 600 km to the south. Additional analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Mastocarpus is a genus with species distributions previously restricted to the North Pacific before it was recorded in Chilean waters nearly four decades ago, and is thus considered an introduced species to the Southern Hemisphere (Lindstrom et al 2011, Macaya et al 2013. Though this non-native species was initially identified as Mastocarpus papillatus (C. Agardh) Kützing (Castilla et al 2005), Lindstrom et al (2011) identified this species as Mastocarpus latissimus (Harvey) S. C. Lindstrom, Hughey & Martone based on an internal transcribed spacer (ITS) sequence from a Chilean specimen, collected at "La Desembocadura" Biobío region.…”
Section: Methodsmentioning
confidence: 99%
“…Mastocarpus is a genus with species distributions previously restricted to the North Pacific before it was recorded in Chilean waters nearly four decades ago, and is thus considered an introduced species to the Southern Hemisphere (Lindstrom et al 2011, Macaya et al 2013. Though this non-native species was initially identified as Mastocarpus papillatus (C. Agardh) Kützing (Castilla et al 2005), Lindstrom et al (2011) identified this species as Mastocarpus latissimus (Harvey) S. C. Lindstrom, Hughey & Martone based on an internal transcribed spacer (ITS) sequence from a Chilean specimen, collected at "La Desembocadura" Biobío region.…”
Section: Methodsmentioning
confidence: 99%
“…fragile Madariaga et al, 2014), A. armata (Ramírez et al, 2007), M. latissimus y S. nicaeensis (Vásquez et al, 2001;Villaseñor-Parada et al, 2014). No obstante, proliferación y/o monopolización del sustrato no ocurre en todo el rango de distribución, sino en sectores específicos de la costa (e.g., C. fragile en el norte chico, Neill et al, 2006;A. armata en el norte grande, Ramírez et al, 2008b; M. latissimus en la costa de Concepción, Macaya et al, 2013), y si bien S. nicaeensis, es bastante frecuente a lo largo de la costa, no es muy abundante en los sitios donde está presente, constituyendo un caso especial de invasión (Villaseñor-Parada et al, 2014).…”
Section: Especies Nativas Introducidas Fuera De Su Rango Natural De Dunclassified
“…Existe evidencia empírica que apoya esta idea, pues Macaya et al (2013) señalan la baja abundancia de M. latissimus en los extremos de su rango de distribución, sugiriendo una creciente expansión; Madariaga et al (2014) basados en modelos de nicho ecológico, identifican varios sitios susceptibles a ser invadidos por C. fragile, donde aún no se tiene reportes de dicha especie; y Contreras et al (2007) indican que la ausencia de S. gracilis en la costa de Chañaral se debe netamente a efectos históricos y no a restricciones ambientales asociadas a altas concentraciones de cobre, que esta especie es capaz de tolerar en condiciones de laboratorio.…”
Section: Especies Nativas Introducidas Fuera De Su Rango Natural De Dunclassified